Improving Students Speaking Skill by Implementing Blended Learning (Online Learning and Classroom) - Makmun Syaifudin (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2017)
This study is aimed at finding out howBlended Learning model is able to improve students’ speaking skill and finding out students’ response toward the implementation of BlendedLearning in speaking class. Classroom action research wasthe research design of this study. It occupied observation, interview and test as the instruments. In Blended Learning, there were two activities which consist of online learning activities which were done using internet and traditional face to face activities which were done in the class. In online learning, the lecturer delivered materials’ using online sources through a whatsup group which has been made before and it is learned and discussed together before face to face class. While in face to face class, the lecturer restated the topic and materials for the students and let them practice speaking a lot. Blended Learning was able to improve students speaking skill and it was proved that the average score of four speaking components in every cycle was improved. The students also had very good response toward the implementation of Blended Learning that they said Blended Learning made their learning more fun and interactive.